New Upstream Records for Fishes Following Dam Removal in the Cahaba River, Alabama - Micah G. Bennett; J. Heath Howell; Bernard R Kuhajda; Paul L. Freeman (Southeastern Fishes Council Proceedings, 2015)
Population fragmentation by dams of all sizes is a major threat to biodiversity in running waters. Dam removal has become an increasingly popular tool among conservation practitioners because of its potential benefits to aquatic organisms and ecosystems. During fish monitoring following removal of a small run-of-river dam on the Cahaba River, we documented new upstream records between 8 months and 2 years post-removal for five species: Stargazer Shiner, Notropis uranoscopus; River Redhorse, Moxostoma carinatum; Southern Sand Darter, Ammocrypta meridiana; Freckled Darter, Percina lenticula; River Darter, P. shumardi. These new records suggest that the former dam may have served as a barrier to dispersal of resident species, and that dam removal may have benefited these species by opening additional habitat to colonization.
Keywords: colonization; dispersal; habitat; peripheral populations